1989
DOI: 10.1016/0014-5793(89)80892-0
|View full text |Cite
|
Sign up to set email alerts
|

An enzyme caught in action: Direct imaging of hydrolytic function and domain formation of phospholipase A2 in phosphatidylcholine monolayers

Abstract: Phospholipase 4, a ubiquitous lipolytic enzyme that actively catalyzes hydrolysis of phospholipids, has been studied as a model for enzyme-substrate reactions, as a membrane structural probe, and as a model for lipid-protein interactions. Its mechanism of action remains largely controversial. We report here for the first time direct microscopic observation of the lipolytic action of fluorescently marked phospholipase 4 (No& naju naja) against phosphatidylcholine monolayers in the lipid phase transition region.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(81 citation statements)
references
References 31 publications
7
73
0
1
Order By: Relevance
“…10 suggest that hydrolysis of biological membranes may be sensitive to boundaries around ordered membrane domains as it is in artificial membranes (50). The data do not distinguish whether sPLA 2 attacked regions of lower GP causing them to shrink or regions of higher GP causing them to expand.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…10 suggest that hydrolysis of biological membranes may be sensitive to boundaries around ordered membrane domains as it is in artificial membranes (50). The data do not distinguish whether sPLA 2 attacked regions of lower GP causing them to shrink or regions of higher GP causing them to expand.…”
Section: Discussionmentioning
confidence: 91%
“…It could be argued that the effect of the fatty acid to promote hydrolysis is due to its negative charge; however, it is equally or more effective at making the membrane susceptible when in the protonated (non-charged) form (15). Finally, microscopic images of hydrolysis of monolayers composed of coexisting solid-phase and liquid-phase phospholipid domains revealed that sPLA 2 preferentially attacks the more ordered solid-phase domains (50). The generalization that emerged from the studies with artificial membranes was that it is not the fluidity of the membrane per se that determines susceptibility, but rather it is the organization of lipids within the bilayer that appears critical.…”
Section: Discussionmentioning
confidence: 99%
“…This accumulation at domain edges implies that attractive forces are acting between Fn in the LE phase and the domains. The insertion of proteins into the LE phase and migration to domain boundaries is not unique to Fn and has been observed for several other proteins (21,(23)(24)(25). Two nonexclusive theoretical models have been proposed to account for the attractive interaction between domain boundaries and surface-adsorbed proteins in the LE phase: attractive dipole͞dipole interactions (26) and entropy-driven depletion forces (27).…”
Section: Resultsmentioning
confidence: 99%
“…After compression of the lipid monolayer, Fn was injected into the buffer subphase along the outside of the Teflon barriers (21), equilibrating at a final concentration of 4 g͞ml.…”
Section: Methodsmentioning
confidence: 99%
“…In two different studies (9,28), it was reported that the enzyme caused substrate degradation of the LC domains beginning from the domain boundary. However, a close analysis reveals that the methodology used in those studies cannot actually ascertain whether the LE phase was not likewise degraded, because substrate degradation within the LE phase cannot be distinguished by the probe used.…”
Section: Perimeter-activated Versus Area-activated Mechanism Of Actiomentioning
confidence: 99%